PENGARUH KELELAHAN PASCA STROKE TERHADAP KESEIMBANGAN DINAMIS PADA LANSIA - Mariel Daba (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
Abstract: This study aims to determine the effect of post-stroke fatigue on motor function as seen from dynamic balance in the elderly. The results of this examination are considered because they are an important component of stroke recovery. The research was conducted at the Sri Mulyani Physiotherapy Clinic, West Jakarta for approximately 1 month, from January to March 2023. The measurement instruments in this study were the FAS to see post-stroke fatigue in the elderly and the Time Up and Go Test (TUG) to see dynamic balance function in the elderly. The results of the study were based on examining post-stroke fatigue using FAS before and after the intervention. There was a significant effect (p value = 0.0001****) in the examination group I, and dynamic balance examination using the TUG before and after the intervention had a significant effect (p value = 0.0004***) in the examination group II. On examination to see the effect of FAS and TUG it was found that there was a significant effect (p value = 0.0001**** or p <0.05) between post-stroke fatigue on dynamic balance in the elderly. The conclusion from the research results is that there is a significant influence between the results of examining post-stroke fatigue in the elderly using the Fatigue Assessment Scale on dynamic balance in the elderly using the Time Up and Go Test.